“Include me if you can”: reasons for low enrollment of pediatric patients in a psychopharmacological trial - Niemeyer, Larissa; Mechler, Konstantin; Buitelaar, Jan; Durston, Sarah; Gooskens, Bram; Oranje, Bob; Banaschewski, Tobias; Dittmann, Ralf; Häge, Alexander (Trials, 2021)
Low recruitment in clinical trials is a common and costly problem which undermines medical research. This study aimed to investigate the challenges faced in recruiting children and adolescents with obsessive-compulsive disorder and autism spectrum disorder for a randomized, double-blind, placebo-controlled clinical trial and to analyze reasons for non-participation. The trial was part of the EU FP7 project TACTICS (Translational Adolescent and Childhood Therapeutic Interventions in Compulsive Syndromes).